ANALISIS PORTOFOLIO DALAM MENENTUKAN INVESTASI SAHAM PADA INDUSTRI OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA - Reni Ariskawati (FE Program Studi Manajemen, 2017)
This study aims to determine the estimated benefits and risks individually as well as the proportion of investment allocation to obtain optimal portfolios in the automotive industry that are listed in the Indonesia Stock Exchange Of Population 13 listed company, selected 10 companies that meet the criteria. Analysis of the results showed that PT Astra International Tbk (ASII) has the greatest return 0.11516796 or 11.5% which is the most optimal stock, it is shown on the value of the highest expected return of the ten stocks with certain risks. Optimum portfolio stock Indo Kordsa Tbk (BRAM) of 0.1245231 (12.4%) with an allocation of 80%, 0.09815386 (9.8%) with an allocation of 20%, 0.1153125 (11.5%) with an allocation of 50%. After the diversification of the companies on the automotive listed on the Indonesia Stock Exchange, was able to reduce the investment risk if only invested in one stock alone. Previous risk ten stocks in the sample had a high risk, but once done diversify portfolio risk value is much smaller. Thus we can conclude that diversification is more effective than simply investing in one stock alone.. Keywords: portofolio optimal